2015
DOI: 10.1038/gim.2014.124
|View full text |Cite
|
Sign up to set email alerts
|

Refinement of the critical 2p25.3 deletion region: the role of MYT1L in intellectual disability and obesity

Abstract: Conclusion:Our data strongly strengthen the hypothesis that MYT1L is the causal gene for the observed syndromal intellectual disability. Moreover, because 17 patients present with obesity/overweight, haploinsufficiency of MYT1L might predispose to weight problems with childhood onset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(76 citation statements)
references
References 25 publications
6
64
0
Order By: Relevance
“…In 2012, a de novo MYT1L splice site mutation was identified as part of a larger study in a girl with ID, autistic features, normal growth, and mild dysmorphism (de Ligt et al, ). After three publications on seven more individuals with microdeletions encompassing MYT1L and global DD/ID, behavioral difficulties/hyperactivity and overweight/obesity (Bonaglia et al, ; Doco‐Fenzy et al, ; Rio et al, ), de Rocker and colleagues published an extensive study on 22 individuals bearing either chromosomal aberrations or SNVs affecting MYT1L (De Rocker et al, ). Seventeen of these 22 individuals presented with obesity/overweight.…”
Section: Discussionmentioning
confidence: 99%
“…In 2012, a de novo MYT1L splice site mutation was identified as part of a larger study in a girl with ID, autistic features, normal growth, and mild dysmorphism (de Ligt et al, ). After three publications on seven more individuals with microdeletions encompassing MYT1L and global DD/ID, behavioral difficulties/hyperactivity and overweight/obesity (Bonaglia et al, ; Doco‐Fenzy et al, ; Rio et al, ), de Rocker and colleagues published an extensive study on 22 individuals bearing either chromosomal aberrations or SNVs affecting MYT1L (De Rocker et al, ). Seventeen of these 22 individuals presented with obesity/overweight.…”
Section: Discussionmentioning
confidence: 99%
“…A role for MYT1L in neural development is further supported by the identification of MYT1L mutations in patients diagnosed with various neurodevelopmental disorders. The identification of mutations on chromosome band 2p25.3 disrupting the MYT1L gene in patients with mild to moderate intellectual disability and speech delay (Bonaglia et al , 2014; de Ligt et al , 2012; De Rocker et al , 2015; Mayo et al , 2015; Stevens et al , 2011) provided the first links between haploinsufficiency of MYT1L and intellectual disability (De Rocker et al , 2015). MYT1L mutations have also been associated with diseases, such as schizophrenia (Lee et al , 2012; Vrijenhoek et al , 2008), autism (De Rubeis et al , 2014; Meyer et al , 2012) and major depressive disorder (Wang et al , 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that peroxidase activity is significantly decreased by regular vomiting [Schlueter et al, 2012], and proteolytic enzymes seem to be relevant for the initiation and progression of dental erosion directly after vomiting, maybe by both hydrolysis of demineralized dentine structures as well as modulation of the pellicle layer [Schlueter et al, 2012]. MYT1L has been reported to be involved in neural development, weight problems of childhood onset and a clinical phenotype of dysmorphic features [Stevens et al, 2011;De Rocker et al, 2015]. Interestingly, a suggestively associated polymorphism in a GWAS of dental caries was observed close to the abovementioned region [Shaffer et al, 2013].…”
Section: Gwas On the Whole Samplementioning
confidence: 99%